PRODUKTIVITAS TENAGA KERJA TERHADAP BIAYA DAN WAKTU PELAKSANAAN PADA PEMBANGUNAN RUKO 2 LANTAI - Siti Abadiyah; Ria Rosyati; Qori Nurjanah (University of Muhammadiyah Tangerang, 2021)
Productivity is the quantity of work a workforce achieves per day. The amount of productivity can be seen from the large quantity of work divided by the time it takes for labor to complete the job. One of the factors that influence the amount of work productivity is the number of workers. One of the factors affecting the amount of work productivity is the number of workers, however the number of workers per day needs to be limited based on the quantity of work and the cost of the project work. Therefore, it is necessary to know the estimated cost of work from the number of workers working on a job. Estimates of work costs are known from the number of workers and the wages of workers per day. From the research results, it is known that the cost of the productivity of the structure construction spent Rp. 223,492,785.00.Keywords: Productivity, labor, time and cost.